1995
DOI: 10.1210/jcem.80.2.7852490
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short and long-term growth hormone replacement therapy in hypopituitary adults on lipid metabolism and carbohydrate tolerance.

Abstract: The effects of replacement with biosynthetic human GH on carbohydrate tolerance and lipid metabolism were studied in 40 hypopituitary adults during a randomized double blind, placebo-controlled trial for 6 months, followed by a 12-month open trial. The daily GH dose was 0.04 +/- 0.01 IU/kg. Fasting plasma glucose, serum fructosamine, plasmid lipids, lipoproteins, and plasma C-peptide concentrations were measured, and an oral glucose tolerance test was performed every 6 months. There was no change in fasting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
4
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 38 publications
11
65
4
2
Order By: Relevance
“…Prospective dose response studies will be necessary to decide this. Our ®nding that HDL cholesterol was unchanged after GH treatment is in accordance with some, 11,17±19,28 but not with other, 15,16,26,29,30 studies in which increased levels were found. The reason for this discrepancy is not readily explained.…”
Section: Discussionsupporting
confidence: 90%
“…Prospective dose response studies will be necessary to decide this. Our ®nding that HDL cholesterol was unchanged after GH treatment is in accordance with some, 11,17±19,28 but not with other, 15,16,26,29,30 studies in which increased levels were found. The reason for this discrepancy is not readily explained.…”
Section: Discussionsupporting
confidence: 90%
“…high triglycerides, low HDL cholesterol, elevated small dense LDL) may be common (14-50%), but complete ALP is relatively uncommon (14% in GHD and 7% after GHRT). Therefore, it remains to be established whether quantitative and qualitative changes of lipids are the main cause for the increased cardiovascular mortality and morbidity found in hypopituitary patients with GHD (39,40). Similarly, the lack of effect of GHRT on LDL size in the present study does not support the concept that a possible effect of GHRT on cardiovascular mortality, as recently suggested (41), is related to the effect of GH on lipid metabolism.…”
Section: Ghd Versus Controls (Pz)contrasting
confidence: 85%
“…In this study, we have not evaluated the plasma levels of low density lipoprotein (LDL)/high density lipoprotein (HDL) cholesterol, but our finding of decreased cholesterol levels in hexarelin-treated obese rats could be due to a decrease in LDL cholesterol with minor changes in HDL cholesterol. In fact, it has been shown in humans that both the GHRP-induced GH release and activation of the HPA axis cause changes in lipoprotein metabolism, decreasing LDL cholesterol and increasing HDL cholesterol (Berg & Nilsson-Ehle 1994, Beshyah et al 1995. Furthermore, changes in the levels of each plasma lipoprotein and, obviously, of total cholesterol seem dependent on the length of GHRP treatment.…”
Section: Discussionmentioning
confidence: 99%